2014
DOI: 10.1002/j.0022-0337.2014.78.5.tb05718.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Portfolio Assessment of Student Competence in Two Dental School Populations: A Four‐Year Study

Abstract: The purpose of this study was to empirically investigate the validity and reliability of portfolio assessment in two U.S. dental schools using a uniied framework for validity. In the process of validation, it is not the test that is validated but rather the claims (interpretations and uses) about test scores that are validated. Kane's argument-based validation framework provided the structure for reporting results where validity claims are followed by evidence to support the argument. This multivariate general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 21 publications
1
36
0
1
Order By: Relevance
“…The transferable skills survey, in particular the four‐factor structure for future transferable skills, also had good discriminant validity to differentiate the students' perception of transferable skills across different dental programmes. Valid instruments with proven reliability and capable of consistent measurements are becoming increasingly important for dental educators who seek to understand their students' perception of transferable skills …”
Section: Discussionmentioning
confidence: 99%
“…The transferable skills survey, in particular the four‐factor structure for future transferable skills, also had good discriminant validity to differentiate the students' perception of transferable skills across different dental programmes. Valid instruments with proven reliability and capable of consistent measurements are becoming increasingly important for dental educators who seek to understand their students' perception of transferable skills …”
Section: Discussionmentioning
confidence: 99%
“…Validity refers to accumulation of the gathered evidence from multiple sources to support the claim that the assessment is indeed evaluating the speciic knowledge and skills being tested. 24 When a new method of testing is contemplated, a validity study to examine format, content, context efects, and ease of use should be conducted prior to implementation. 13 The results of this study found moderate correlation of the AR virtual tooth identiication test and the traditional real tooth identiication test with other criterion measures used to determine student performance in the dental anatomy course.…”
Section: Question 3 Accuracy 24mentioning
confidence: 99%
“…Like many U.S. dental schools over the last 25 years, the University of California, San Francisco (UCSF) School of Dentistry has employed various clinical curricula to ensure students obtain adequate clinical experience and attain required competencies for graduation. Dental schools have introduced such innovative curriculum and assessment formats as comprehensive care, 1 6 case completion, 7 , 8 competency examinations, 9 12 portfolios, 13 , 14 and community‐based, off‐campus externships 15 17 . UCSF has had three major clinical curricular changes since 1992, moving from a discipline‐based curriculum to a comprehensive care curriculum to a procedural requirement curriculum plus externships.…”
mentioning
confidence: 99%